Функції монологічного мовлення в епістолярному жанрі - Крищук, В. (Філологічний дискурс, 2018)
У статті доведено, що епістолярний стиль мови, сфера його використання необмежена – у листі може йти мова про творчі плани, побут, інтимне життя, політику, релігію, науку, освіту чи виробництво. Основне ж призначення мови – це заочне спілкування у монологічному форматі, писемно оформленій матриці, а тематика залежить від сфери їх впливу, зацікавленості обох сторін (адресанта й адресата), сформованого світогляду, мовної культури. Епістолярій не лише має приватний характер, а й історичний, суспільно- культурний інтерес, що доведено під час аналізу листів літераторів української еміграції Павла Богацького та Юрія Шевельова. Досліджено функції монологічного мовлення в епістолярному жанрі в різновекторних аспектах їх використання. It is proved in the article that the epistolary style of the language, the scope of its use is unlimited – the letter can be about creative plans, mode of life, intimate life, politics, religion, science, education or production. The main purpose of the language is the absentee communication in the monologue format, the matrix, designed in the written form; and the subject matter depends on the sphere of their influence, the interest of both parties (the addresser and the addressee), the formed world outlook, the linguistic culture. The epistolary doesn’t only have private character, but also it has historical, socio-cultural interest, that is proved during the analysis of the letters of Ukrainian emigration writers Pavlo Bohatskyi and Yurii Sheveliov. The functions of monological speech in the epistolary genre in variousvector aspects of their use have been studied. It is cleared out that the central purpose of the epistolary style is to serve correspondence, in the form of letters, communication of people in all spheres of their life. The letters can vary by the subjects and the content, depending on the scope of their application and the interests of communicants. It is known that correspondence is divided into two types: official (service) and informal (private). However, in addition to letters to the epistolary style, they include diaries, memoirs, reports, notes, calendars. In the article, we have analyzed the letters in which the functions of the monological speech are revealed – informative, ritual-religious, expressive (emotional-significant), meta-communicative, influential and didactic (instructive) functions. At the psychological level, the monological speech relies on thinking, logically consecutive presentation of thought with the awareness of the written speech action, which is aimed at the result. The author, when writing, can experience, worry, re-read the letter several times before sending to the addressee. The text of the writer’s epistle contains aesthetic ideas and, figuratively speaking, «wears rich clothes» by expressive-figurative means. The article comprehensively reveals the peculiarities of the epistolary genre in the aspect of the functional segment of monological speech.